Função sexual e autoimagem corporal: um estudo comparativo entre mulheres adultas em idade reprodutiva e idosas - Souza, Cora da Gama (2022)
In order to bring to light an intergenerational discussion, since perceptions about sexuality, as well as the constant changes of the contemporary world and the aesthetic demands that plague women's bodies, have undergone several changes over the years, this work is a study that aims to compare the sexual function and body self-image of women of reproductive age with elderly women, residents of a city of Rio Grande do Sul. Observational research, with a quantitative approach and transversal character, with women aged 18 to 44 years. The data collection was carried out through a virtual interview and the compared data of elderly women were derived from the research “Factors that interfere with the genital self-image of elderly women”. Both studies derive from the project entitled “Relationship between pelvic floor pain, sexual function and genital self-image of elderly women with and without fibromyalgia”, approved by the Research Ethics Committee of UFSM under the CAAE number: 80587517.0.0000.5346. All studies are linked to the Post-Graduate Program in Gerontology, at the Federal University of Santa Maria. The instruments used for this research are: Adapted Evaluation Form, Female Sexual Function Index, Female Genital Self-Image Scale e Body Appreciation Scale. To determine the population sample for this study, a pilot project was carried out with 10 women, respecting inclusion and exclusion criteria. Women of reproductive age, from 18 to 44 years old, who have already started their sexual life, and residing in the city of Santa Maria/RS, were included in the research. Of the excluded ones; postpartum women up to 45 days postpartum, pregnant women, women undergoing cancer treatment and who have cognitive deficits that compromise the answers to the questionnaires. Data analyzes were performed using the software Statistical Package for the Social Sciences (SPSS). For asymmetric variables, the non-parametric Mann-Whitney test was performed and the significance level adopted was 5%. Results: the sexual function of older women was poor (22.4) compared to women of reproductive age (30.2). Regarding body self-image, the rate of elderly women was higher (5) than adult women (4.1). It is concluded that it is possible to observe significant changes when comparing different generations of women in terms of sexuality and body self-image, thus showing possible advances in terms of freedoms and empowerments, as well as some influences still socially determined.